Terrorism and Violence between the Islamic Political Perspective and the Duplication of Western concepts - Mustafa Farooq Majeed; Khudhir Abbas Atwan (Tikrit Journal For Political Science, 2022)
The idea of ​​the research revolves around a topic, that Islamic Sharia represents the conclusion of the permanent laws that the Creator established for the children of Adam, and it cannot be said that the Creator placed in it what harms humanity, in its existence or what restricts its freedom, or that its provisions do not fit our world today, otherwise we would have We have come across referring to His inability to know what will happen in human life. Today's terminology of violence varies between: violence, crime, terrorism and other innovative political terms, but the Arabic language gives a wide space for these terms, and the differences between them. Islamic Sharia did not support violence, except in a limited legally justified scope, and it has always been looking for options that allow room for choice and tolerance, but at the same time it allows wide options in jurisprudence, without imposing restrictions on it except within the scope of achieving the supreme interest of Sharia, the country, society and individuals.